2017
DOI: 10.3758/s13423-017-1240-9
|View full text |Cite
|
Sign up to set email alerts
|

On the distinction between value-driven attention and selection history: Evidence from individuals with depressive symptoms

Abstract: When predictive of extrinsic reward as targets, stimuli rapidly acquire the ability to automatically capture attention. Attentional biases for former targets of visual search can also develop without reward feedback, but typically require much longer training. These learned biases towards former targets are often conceptualized within a single framework, and might differ merely in degree. That is, both are the result of the reinforcement of selection history, with extrinsic reward for correct report of the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 33 publications
6
17
0
Order By: Relevance
“…The presence of reward-signaling stimuli slowed down responses compared with their absence, but there was no difference toward lower reward in their first experiment or an unrewarded condition in their second experiment. These and other findings confirm that stimuli that appeared simultaneously with nonrewarded target stimuli can bias attention later (Anderson, Chiu, DiBartolo, & Leal, 2017;Sha & Jiang, 2016;Wang, Yu, & Zhou, 2013). On the other hand a number of experiments did not find any search-driven attentional capture (Anderson et al, 2011a(Anderson et al, , 2014bLaurent, Hall, Anderson, & Yantis, 2015;Qi, Zeng, Ding, & Li, 2013).…”
supporting
confidence: 70%
“…The presence of reward-signaling stimuli slowed down responses compared with their absence, but there was no difference toward lower reward in their first experiment or an unrewarded condition in their second experiment. These and other findings confirm that stimuli that appeared simultaneously with nonrewarded target stimuli can bias attention later (Anderson, Chiu, DiBartolo, & Leal, 2017;Sha & Jiang, 2016;Wang, Yu, & Zhou, 2013). On the other hand a number of experiments did not find any search-driven attentional capture (Anderson et al, 2011a(Anderson et al, , 2014bLaurent, Hall, Anderson, & Yantis, 2015;Qi, Zeng, Ding, & Li, 2013).…”
supporting
confidence: 70%
“…(a) Correlations between the RT costs associated with the high-value distractor (relative to distractor-absent trials), observed at Visit 1 and Visit 2. (b) Correlations between the percentages of trials on which the high-value distractor was the initially fixated stimulus, observed at Visit 1 and Visit 2 fixations to a previously reward-associated stimulus could offer a window on meaningful changes in susceptibility to value-driven attentional capture over time, a construct that has been linked to a variety of psychopathologies (Anderson et al, 2013;Anderson, Chiu, et al, 2017;Anderson, Kronemer, et al, 2016;Anderson, Leal, et al, 2014;Sali et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence points to a possible role for value-driven attention in psychopathology. The degree to which an arbitrary reward cue impairs performance in an attention task has been linked to drug dependence (Anderson, Faulkner, Rilee, Yantis, & Marvel, 2013;Anderson, Kronemer, Rilee, Sacktor, & Marvel, 2016; see Anderson, 2016b, for a review), HIV-risk behaviors (Anderson, Kronemer, et al, 2016), depression (Anderson, Chiu, DiBartolo, & Leal, 2017;Anderson, Leal, et al, 2014), and attention deficit/hyperactivity disorder (Sali, Anderson, Yantis, Mostofsky, & Rosch, 2018). Attention to reward covaries with the presence of these psychopathologies and may play a role in the observed symptomology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One the one hand, reward-associated stimulus was found to elicit quantitatively similar attentional capture effect as previous selected target during training (Sha & Jiang, 2016 ). On the other hand, reward association and selection history have also been shown to have distinct effects (Anderson & Halpern, 2017 ; Anderson, Chiu, DiBartolo, & Leal, 2017 ). The present study minimized the contribution of selection history in the first place, not only by adopting equivalent training for the coherent and random motion stimuli, but also de-emphasizing explicit selection during training because participants were presented with one stimulus at a time and responded to the change of speed.…”
Section: Discussionmentioning
confidence: 99%